Web-based wireless data acquisition system using 32bit single board computer - R. Badlishah, Ahmad; Wan Muhamad Azmi, Mamat; Mohamad Rizon, Mohamed Juhari; Shuhaizar, Daud; Arshad, N.W. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org